Near Peer Mentors to Address Socio-Emotional Issues Among Underrepresented Minority High School Students in Research Intensive STEM Programs: Perceptions of Students and Mentors - Qua, Kelli (J STEM Outreach, 2020)
A Near Peer Mentoring Program (NPMP) was developed in which Medical Student Training Program (MSTP) students met weekly with small groups of high school students who were participating in an intensive summer biomedical research immersion program. The goal of the NPMP was to provide and engage the high school students with opportunities to express and discuss their research and more importantly, their stresses and concerns. After initial reservations, the NPMP provided a comfortable venue for high school students to engage in discussions of both laboratory and personal topics. Overall, their concerns and stresses were expressed in five categories: 1) College Preparation, 2) Preparation for MD and PhD Training and Careers, 3) Summer Research Programmatic Issues and Laboratory Social Structure, 4) Social Issues, and 5) Health and Wellness. High school students identified the following major factors as contributing to programmatic success: relatability, role models, comfort and approachability, organization, and mentor fit. The Near Peer Mentoring initiative revealed the need for STEM and other programs targeting academic success and career development to be alert to social and emotional concerns of students and to provide opportunities for their expression, discussion and guidance.